Evaluation of Pedestrian Pathways on The UKSW Blotongan Campus Landscape on An Ecological Base - Amaris, Lidya Fayza; Sutrisno, Alfred Jansen (Ruwa Jurai: Jurnal Kesehatan Lingkungan, 2024)
The pedestrian pathways within campus environments play a crucial role in ensuring safety, comfort, and efficient mobility for campus users. At the UKSW Blotongan Campus, there are several deficiencies in the pedestrian pathways that need to be addressed, especially concerning the needs of persons with disabilities and the lack of facilities such as traffic signs and dedicated bike lanes. Moreover, pedestrian pathways should also contribute to improving the surrounding environment. Therefore, the aim of this research is to evaluate the pedestrian pathways on campus and provide practical suggestions for their improvement and development. The method used is purposive sampling involving 20 trees with a diameter >50 cm, which includes an inventory of existing conditions, analysis of carbon absorption and plant dust absorption, and comparison with technical standards. The analysis results show that the Sesbania grandiflora tree (Kembang Turi) can significantly absorb carbon and dust. Based on the analysis results, recommendations can be made for the sustainable and environmentally friendly improvement of pedestrian pathways at the UKSW Blotongan Campus.